Medical Robotics - New Achievements 2020
DOI: 10.5772/intechopen.90642
|View full text |Cite
|
Sign up to set email alerts
|

Ureteropelvic Junction Obstruction: Robot-Assisted Pyeloplasty

Abstract: The standard treatment of ureteropelvic junction obstruction (UPJO) is represented by the Anderson-Hynes dismembered pyeloplasty, even if different approaches, both surgical and endoscopic, have been described. Robot-assisted pyeloplasty (RP) is a feasible and safe approach. The indications for the robotic approach remain the same as those for the laparoscopic or open pyeloplasty. Every patient with symptomatic UPJO, or with decreasing renal function in the presence of UPJO, should undergo RP. The transperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(53 reference statements)
0
2
0
Order By: Relevance
“… 43 Surgical precision and extended maneuverability provided by the robotic system were amongst the main advantages of this approach, which facilitated better dissection, thus reducing blood loss and increasing suture quality. 44 In addition, with a success rate ranging from 94% to 100%, robotic pyeloplasty was also effective in children underwent secondary pyeloplasty and complex procedure such as in ureterocalicostomy for recurrent PUJO or intrarenal uretero-pelvic junction. 45 Oderda et al observed that robotic surgery was an excellent choice in treating PUJO patients complicated with horseshoe kidney in both paediatric and adult patients.…”
Section: Minimal Invasive Treatment In Pujomentioning
confidence: 98%
See 1 more Smart Citation
“… 43 Surgical precision and extended maneuverability provided by the robotic system were amongst the main advantages of this approach, which facilitated better dissection, thus reducing blood loss and increasing suture quality. 44 In addition, with a success rate ranging from 94% to 100%, robotic pyeloplasty was also effective in children underwent secondary pyeloplasty and complex procedure such as in ureterocalicostomy for recurrent PUJO or intrarenal uretero-pelvic junction. 45 Oderda et al observed that robotic surgery was an excellent choice in treating PUJO patients complicated with horseshoe kidney in both paediatric and adult patients.…”
Section: Minimal Invasive Treatment In Pujomentioning
confidence: 98%
“…43 Surgical precision and extended maneuverability provided by the robotic system were amongst the main advantages of this approach, which facilitated better dissection, thus reducing blood loss and increasing suture quality. 44 In addition, with a success https://doi.org/10.2147/RRU.S268569…”
Section: Robotic Surgerymentioning
confidence: 99%